A Physically Based Model to Predict Microstructural Modifications in Inconel 718 High Speed Machining - Rinaldi, Sergio; Umbrello, Domenico; Rotella, Giovanna; Prete, Antonio Del (Procedia manufacturing, 2020)
Inconel 718 nickel-based super alloy is widely used in aerospace, nuclear and marine industries due to its important thermo-mechanical properties and excellent corrosion resistance. Despite of its good mechanical performance, this alloy is extremely difficult to be machined. Moreover, high speed machining processes can radically affect the products quality in terms of surface integrity, because of metallurgical modifications induced by severe thermo-mechanically induced loads. Physics based computational analysis is an excellent technique to analyze the micro-scale phenomena (e.g. dynamic recrystallization, density of dislocation changes, etc.) occurring during the large plastic deformation induced by the industrial processes. Thus, it represents an important tool to optimize the cutting process, allowing to achieve the desired surface integrity on the machined parts. This work employ a physics based model to assess the micro-mechanical behavior of Inconel 718 super alloy subject to severe machining operations at extremely high speed. Results show the good capability of the model to properly deal with the microstructural modifications occurring during the process and to predict the main variables of industrial interest.